Utilization of kitchen waste for the production of green thermoplastic polyhydroxybutyrate (PHB) by Cupriavidus necator CCGUG 52238 - Omar, Farah Nadia; Abdul Rahman, Nor'aini; Hafid, Halimatun Saadiah; Mumtaz, Tabassum; Phang, Lai Yee; Hassan, Mohd Ali (Academic Journals, 2011)
Polyhydroxybutyrate (PHB) was produced by Cupriavidus necator CCGUG 52238 using organic acids from fermented kitchen waste. HPLC and nuclear magnetic resonance (NMR) analyses revealed that the acid comprised mainly of lactic and acetic acids. In shake flask culture, the lactic acid concentration above 10 g/L inhibited both cell growth and polyhydroxybutyrate (PHB) production. The PHB production by the strain was achieved at the highest PHB content of 52.79% in batch fermentation using the kitchen-waste derived organic acids. The PHB yield and productivity were 0.38 g/g and 0.065 g/L/h, respectively. In fed-batch culture, about 4-fold increase in PHB productivity (0.242 g/L/h) was achieved by applying intermittent feeding strategy.